2023
DOI: 10.3390/polym15234494
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Interactions between Soft Segments in Polyurethanes: Structural Synergies in Blends of Polyester and Polycarbonate Diol Polyols

Yuliet Paez-Amieva,
José Miguel Martín-Martínez

Abstract: There are no previous studies on the interactions between polyols of different nature as a model for understanding the interactions between soft segments in PUs. In this study, different blends of two polyols of different natures (polyester—PE, and polycarbonate diol—CD) and similar molecular weights were prepared and their structural, thermal, surface, viscoelastic, and self-adhesion properties were assessed. Different experimental techniques were used: infrared spectroscopy (ATR-IR), differential scanning ca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…In fact, the polyols (CD and PE) show diffraction peaks at the same 2θ values as their corresponding PUs (Figure 12), and, therefore, the crystallinity of YCD and YPE should derive from the interactions between the soft segments. The diffraction peaks at 2θ values of 21 • and 22 • in PE polyol have been ascribed to ester-ester interactions and the ones at 20 • and 23 • to carbonate-carbonate interactions in CD polyol [84]. On the other hand, the intensities of the diffraction peaks of YPE are higher than the ones of YCD (Table 3) and they are lower than the ones of the corresponding polyols (Table 4), to a greater extent in YPE.…”
Section: Wavenumber (Cmmentioning
confidence: 88%
See 3 more Smart Citations
“…In fact, the polyols (CD and PE) show diffraction peaks at the same 2θ values as their corresponding PUs (Figure 12), and, therefore, the crystallinity of YCD and YPE should derive from the interactions between the soft segments. The diffraction peaks at 2θ values of 21 • and 22 • in PE polyol have been ascribed to ester-ester interactions and the ones at 20 • and 23 • to carbonate-carbonate interactions in CD polyol [84]. On the other hand, the intensities of the diffraction peaks of YPE are higher than the ones of YCD (Table 3) and they are lower than the ones of the corresponding polyols (Table 4), to a greater extent in YPE.…”
Section: Wavenumber (Cmmentioning
confidence: 88%
“…The assignment of the thermal degradations is based on the DTGA curves of the polyols (Figure 14) that only show one main thermal degradation at 340 • C and 352 • C, respectively. These thermal degradations have ascribed to carbonate-carbonate and ester-ester interactions, respectively [84]. Previous studies have shown that the TGA curves of PUs show differenced thermal degradations of the hard and soft segments [66,80].…”
Section: Wavenumber (Cmmentioning
confidence: 97%
See 2 more Smart Citations